2017
DOI: 10.1002/gps.4673
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and incident depression in community‐dwelling older people: results from the ELSA study

Abstract: Among older community dwellers, frailty and pre-frailty did not predict the onset of depression during 2 years of follow-up, when accounting for potential confounders, whilst slow gait speed considered alone may predict depression in the older people. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 46 publications
1
49
0
1
Order By: Relevance
“…A previous cross‐sectional study reported that reduced physical performance, that is slower comfortable walking speed, was a difference between robust and frail individuals . Another 2‐year longitudinal study reported that comfortable walking speed was a predictor of frail and pre‐frail status . Frailty and depressive state or reduced sociality have been found to be mutually related; one study reported that cognitive function on the MMSE was closely related to reduced sociality and increased risk of frailty .…”
Section: Discussionmentioning
confidence: 99%
“…A previous cross‐sectional study reported that reduced physical performance, that is slower comfortable walking speed, was a difference between robust and frail individuals . Another 2‐year longitudinal study reported that comfortable walking speed was a predictor of frail and pre‐frail status . Frailty and depressive state or reduced sociality have been found to be mutually related; one study reported that cognitive function on the MMSE was closely related to reduced sociality and increased risk of frailty .…”
Section: Discussionmentioning
confidence: 99%
“…1 Frailty is a common condition in the elderly, with a prevalence of 10% for those older than 65 years and 30% for those older than 80 years. 2,3 Frailty is significantly associated with several deleterious outcomes in the elderly, including depression 4,5 , cardiovascular disease 6 , hospitalization 7 and, in some instances, mortality. 8 Consequently, understanding, preventing and managing frailty in older adults is of high importance.…”
Section: Introductionmentioning
confidence: 99%
“…45 An English longitudinal study with 4,077 subjects over 60 years old pointed out that depressive symptoms are considered a risk factor for the gait speed component in older residents. 46 Limitations were detected in the present study. The cross-sectional method does not allow the establishment of causality between the variables frailty and depressive symptoms.…”
Section: Discussionmentioning
confidence: 54%